Disgust Sensitivity Among Women During the COVID-19 Outbreak - Miłkowska, Karolina; Galbarczyk, Andrzej; Mijas, Magdalena; Jasienska, Grazyna (Frontiers in Psychology, 2021)
The emotion of disgust is suggested to be an adaptation that evolved to keep us away from sources of infection. Therefore, individuals from populations with greater pathogen stress should have a greater disgust sensitivity. However, current evidence for a positive relationship between disgust sensitivity and the intensity of infectious diseases in the environment is limited. We tested whether disgust and contamination sensitivity changed in response to the COVID-19 pandemic. Disgust was assessed in 984 women in 2017 (before pandemic) and 633 women in 2020 (during pandemic) by a set of photographs depicting sources of infection and Pathogen and Moral of Three-Domain Disgust Scale. Further, contamination sensitivity among participants in two waves was measured by Contamination Obsessions and Washing Compulsions Subscale of Padua Inventory. State anxiety was measured with the Polish adaptation of the State-Trait Anxiety Inventory (STAI) only during the second wave of data collection. Women from the COVID-19 pandemic group assessed the photographs depicting sources of infection as more disgusting, scoring higher on Padua Inventory, but lower on Moral Disgust Domain as compared to women from before the pandemic. In addition, anxiety levels during pandemic positively correlated with scores from Pathogen Disgust Domain, Padua Inventory, and the ratings of the photographs. The participants of the study scored higher in state anxiety than the norms determined for the Polish population. Summarizing, we present evidence for differences in individual levels of disgust sensitivity in relation to pathogen stress, supporting the idea that disgust evolved to serve as protection from pathogens.